Pengaruh Latihan Quarter Squat Jump Terhadap Kecepatan Tendangan Bola Pada SSB Putra Mandiri Semarang - Taufiq Hidayah; Reza Agustian Putra (Tadulako Journal Sport Sciences And Physical Education, 2023)
This study aims to find out whether there is a significant effect of quarter squat jump training on ball kick speed. This study used a quantitative method of experimental research with a one group pretest-posttest design . The sample in this study were U-12 students at Putra Mandiri Semarang football school, a total of 16 athletes. This research was conducted for 12 meetings with a frequency of exercise 4 times a week. The test instrument for this study used a shooting test instrument . The result of the average pretest is 1051,25 and the result of the average posttest is 1111. The results of the study through paired t-test showed t count -6.63 <t table 2,13145 and a significance value of 0.001 <0.05. Based on the results of this analysis, it can be concluded that there is an effect of quarter squat jump training on ball kick speed at SSB Putra Mandiri Semarang.